Novel body positioning maximizes femoral venous size in adults: An ultrasonographic evaluation. Issue 6 (November 2018) - Ahn, Hong Joon; Lee, Jun Wan; Yoo, Seung Woo; Kim, Jee Hyun; Kim, Kun Dong; Yoo, In Sool; Kim, Cuk-Seong
Introduction: Increased femoral vein size may lead to a higher first pass success rate during central venous cannulation. The aim of this study was to evaluate the effects of body position on femoral vein anatomy for cannulation. Methods: This prospective study examined the femoral vein of healthy volunteers by ultrasound scanner. The changes in cross-sectional area and diameter of the femoral vein were evaluated. Right-sided measurements were taken at four different leg positions: neutral, frog leg, back-up, and back-up/frog leg position. Results: A total of 50 subjects were enrolled in the study. The mean femoral vein cross-sectional area were 0.57 ± 0.29 cm 2, 0.90 ± 0.26 cm 2, 1.05 ± 0.33 cm 2, and 1.47 ± 0.34 cm 2, and the mean femoral vein diameter were 0.75 ± 0.20 cm, 1.05 ± 0.28 cm, 1.25 ± 0.21 cm, and 1.46 ± 0.25 cm in order of neutral, back-up, frog leg, and back-up/frog leg position (p < 0.001). Conclusion: Performing the right femoral vein catheterization in back-up and frog leg position is associated with a greater cross-sectional area of the femoral vein.